English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Suppose f(x) = x/2, g(x) = x-3, and h(x) = (sqrt) x

Simplify: h(f(32))

2006-12-18 06:06:10 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

h(f(x)) = sqrt(f(x)) = sqrt(x/2)

so

h(f(32)) = sqrt(32/2) = sqrt(16) = 4

(or -4)

2006-12-18 06:09:55 · answer #1 · answered by Jim Burnell 6 · 0 0

F(32)=32/2=16
h(f(32))=square root of 16=4

2006-12-18 14:19:06 · answer #2 · answered by eissa 3 · 0 0

First : f(32) = 32/2 = 16
Then : h(16) = sqrt(16) = 4

2006-12-18 14:17:32 · answer #3 · answered by Sophia 1 · 0 0

4. you put 32 into f and then the answer (16 into h)

2006-12-18 14:09:25 · answer #4 · answered by !{¤©¤}! 4 · 0 0

the answer is 4

2006-12-18 14:09:08 · answer #5 · answered by net lover 3 · 0 0

fedest.com, questions and answers